EFFECTS OF TYPE 2 DIABETES MELLITUS ON CLINICAL AND LABORATORY STATUS OF WOMEN WITH ARTERIAL HYPERTENSION, OBESITY, AND LEFT VENTRICULAR DIASTOLIC DYSFUNCTION - N. Kyrychenko; N. Opolonska; O. Stepanets (Eastern Ukrainian Medical Journal, 2019)
Patients with type 2 diabetes mellitus (DM) may develop cardiomyopathy independently of such risk factors as arterial hypertension and coronary heart disease. Myocardial dysfunction in diabetes mellitus may vary from subclinical forms of left ventricular dysfunction to heart failure. It was suggested that diastolic left ventricular dysfunction is one of the earliest signs of myocardial injury in diabetes mellitus and plays a key role in the formation of diabetic cardiomyopathy. The aim of our study was to evaluate the effect of diabetes on the clinical and laboratory status of women with hypertension, obesity, and left ventricular diastolic dysfunction (LVDD). Materials and methods. We examined 80 patients aged 40 to 60 years with stage 2, grade II and grade III hypertension, class I–III obesity, grade 1 LVDD and preserved ejection fraction. Depending on the presence or absence of diabetes, the cohort of patients was divided into two groups: patients with diabetes were assigned to group 1 and non-diabetes patients – to group 2. Statistical processing was performed using Statistica for Windows version 6.0. Results. Patients had tendency to increased body mass index (BMI) in the DM group, but without significant differences. The results of the 6-minute walk test showed a tendency to decreased distance in the group of patients with diabetes. There was an increase in leptin levels and a decrease in adiponectin in patients with diabetes without significant differences. Levels of IL-6, glycosylated hemoglobin, and Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) index were significantly higher in the cohort of patients with diabetes (p <0.05). Conclusions. Women aged 40–60 years with LVDD with hypertension, class I–III obesity and type 2 diabetes mellitus differ from similar cohorts of patients without diabetes with a tendency to increased BMI levels, leptinemia, and decrease in distance of 6-minute walk test, LV ejection fraction and blood adiponectin level; they have significantly higher blood levels of interleukin-6, glycosylated hemoglobin (HbA1c) and HOMA-IR; indicators of diastolic function in the group of patients with diabetes tend to worsen the parameters of diastolic filling of the LV even in grade 1 DD.